Risk Factors for Clinically Relevant Postoperative Pancreatic Fistula (CR-POPF) after Distal Pancreatectomy: A Single Center Retrospective Study - Gao Qing Wang; Dipesh Kumar Yadav; Wei Jiang; Yong Fei Hua; Cai De Lu (Canadian Journal of Gastroenterology and Hepatology)
Objectives. Clinically relevant postoperative pancreatic fistula (CR-POPF) is the considerable contributor to major complications after pancreatectomy. The purpose of this study was to evaluate the potential risk factor contributing to CR-POPF following distal pancreatectomy (DP) and discuss the risk factors of pancreatic fistula in order to interpret the clinical importance. Methods. In this retrospective study, 263 patients who underwent DP at Ningbo Medical Center Li Huili Hospital between January 2011 and January 2020 were reviewed in accordance with relevant guidelines and regulations. Patients’ demographics and clinical parameters were evaluated using univariate and multivariate analyses to identify the risk factors contributing to CR-POPF. P<0.05 was considered statistically significant. Results. In all of the 263 patients with DP, pancreatic fistula was the most common surgical complication (19.0%). The univariate analysis of 18 factors showed that the patients with a malignant tumor, soft pancreas, and patient without ligation of the main pancreatic duct were more likely to develop pancreatic fistula. However, on multivariate analysis, the soft texture of the pancreas (OR = 2.381, 95% CI = 1.271–4.460, P=0.001) and the ligation of the main pancreatic duct (OR = 0.388, 95% CI = 0.207–0.726, P=0.002) were only an independent influencing factor for CR-POPF. Conclusions. As a conclusion, pancreatic fistula was the most common surgical complication after DP. The soft texture of the pancreas and the absence of ligation of the main pancreatic duct can increase the risk of CR-POPF.